Empathy among the members of isolated culture - Agnieszka Lewicka-Zelent; K. Korona (Khmelnytskyi Humanitarian-Pedagogical Academy, 2012)
This article presents a look at the resocialization, as a cultural offer, which were presented for imprisoned persons. Perceiving the phenomenon of the prison subculture, as a threat to the future readaptation, a program with using elements of drama was suggested and presented whether and what scope he can contribute to the increase in the level of empathy in.